Neddylation modification of ribosomal protein RPS27L or RPS27 by MDM2 or NEDP1 regulates cancer cell survival. Issue 10 (11th August 2020) - Xiong, Xiufang; Cui, Danrui; Bi, Yanli; Sun, Yi; Zhao, Yongchao
Abstract: Neddylation plays a distinct role in stabilization of a subset of ribosomal proteins. Whether the family of ribosomal proteins S27 (RPS27 and RPS27‐like) is subjected to neddylation regulation with associated biological consequence is totally unknown. Here, we report that both family members are subjected to neddylation by MDM2 E3 ubiquitin ligase, and deneddylation by NEDP1. Blockage of neddylation with MLN4924, a small molecule inhibitor of neddylation‐activating enzyme, destabilizes RPS27L and RPS27 by shortening their protein half‐lives. Biologically, knockdown of RPS27L and RPS27 sensitizes, whereas ectopic expression of RPS27L and RPS27 desensitizes cancer cells to MLN4924‐induced apoptosis. Taken together, our study demonstrates that neddylation stabilizes RPS27L and RPS27 to confer the survival of cancer cells.